The Ethical-Professional Disciplinary Law and its place in the Colombian legal order - Maldonado Sierra, Guillermo Alfonso (DIXI, 2020)
Objective: To describe the general characteristics of the ethical-professional disciplinary law in Colombia.Methodology: A qualitative, documentary, descriptive and deductive historical study was carried out, based on the disciplinary regimes of fourteen professional codes of ethics of some of the most traditional professions in the country that have been regulated by the Colombian legislator.Findings: An approach to the concept of ethical-professional disciplinary law, its legal nature, its substantial differences with disciplinary law, its relationship with the Colombian system of regulatory sources, and a description of its main legal-procedural institutions was achieved.Conclusions: The enormous influence that ethical-professional disciplinary law receives from disciplinary law and criminal law was verified, and a disparity was evident between the disciplinary regimes of the professional codes of ethics analyzed, since some stand out for their procedural guarantees, while those issued prior to the 1991 Constitution are lagging behind, so it is urgent to update them to bring them in line with the constitutional and conventional standards that govern the matter.
Keywords: disciplinary law; ethics courts; professional associations; professional councils; professional ethics; deontology